Effect of macular vascular density on visual quality in young myopic adults - Wang, Xueqing; Xia, Likun (Frontiers in Medicine, 2022)
Objective: To evaluate macular vascular density using optical coherence tomography angiography (OCTA) and to investigate its impact on best-corrected visual acuity (BCVA), contrast sensitivity function (CSF), and higher-order aberrations (HOAs) in young myopic adults. Methods: This cross-sectional study included 109 eyes with AL between 22-26 mm in the medium AL group and 90 eyes with AL >26 mm in the long AL group. OCTA was used to obtain 3×3 mm en face images, and the vessel length density (VLD), perfusion density (PD), and fovea avascular zone (FAZ) of the superficial layer were evaluated. Visual quality was assessed using the CSF and HOAs. Results: Significant differences were found in the inferior VLD, parafoveal PD, and FAZ areas between the groups. AL and macular vascular density showed negative correlations in the inferior and nasal areas. The SE also showed a positive correlation with vascular density in these two areas. FAZ area and perimeter had a significant negative association with AL, and FAZ circularity was correlated with SE. CSF with bright around 6 and 12 spatial frequencies showed positive correlations with nasal PD. The parafoveal PD showed a significant correlation with BCVA after adjusting for other factors. Conclusion: The superficial macular vascular density of young myopic adults decreased with lower SE and longer AL in the parafovea area. An eye with a long AL has a smaller FAZ, and myopia decreases the FAZ circularity index. The decrease in vessel density could contribute to worse BCVA and may be correlated with lower CSF, but not with HOAs.